'Am I really hungry?' A qualitative exploration of patients' experience, adherence and behaviour change during hunger training: a pilot study. Issue 12 (31st December 2019) - de Bruin, Willemijn E; Ward, Aimee L; Taylor, Rachael W; Jospe, Michelle R
Abstract : Objectives: Hunger training (HT) is an intervention designed to teach people to eat according to their hunger by connecting physical symptoms of appetite with glucose levels. HT is most effective for weight loss, and improving eating behaviours when adherence is high. However, adherence is a challenge that should be explored prior to wider dissemination. The aim of this study was to explore participants' experience and self-reported adherence and behaviour change related to HT. Design: A qualitative study, nested within a randomised controlled pilot study of two different methods of monitoring glucose during HT. Semistructured interviews were audio-recorded, transcribed verbatim and analysed thematically using a phenomenological approach. Setting: Single-centre study with participants recruited from the local area. Participants: 40 participants began the pilot study and 38 participants (52.6% women) remained at 1 month and completed interviews. Results: Most participants felt they were able to match their hunger to their glucose levels by the end of the intervention. The main adherence barriers were the social pressure to eat, lack of time and lack of flexibility in participants' meal schedules. Common adherence enablers were having a set routine, social support and accountability. Participants described increased awareness of hungry versus non-hungry eating and better cognition of feelings of hunger and satiety as a result of the intervention, which in turn led to changes of food choice, portion size and adjusted meal timing and frequency. Conclusions: Findings show that HT is acceptable from a patient perspective, and results can be used to inform the translation of HT programme to healthcare settings. Trial registration number: ACTRN12618001257257.